Analisis Pengaruh Penambahan Aditif Tawas Terhadap Compressive Strength dan Setting Time pada Semen Pemboran Kelas G - Timothy Brian Tambuwun; Baiq Maulinda Ulfah; Irma Andrianti (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
Cementing is an important stage in drilling operations that requires cement quality control to provide appropriate strength and setting time. This study aims to analyze the effect of adding alum additives on the mechanical properties and setting time of drilling cement. Tests were conducted using the Compressive Strength and Setting Time method with variations in alum concentration of 0%, 1%, 2%, 3%, and 4% BWOC. The results show that the Compressive Strength value increases with increasing alum concentration, from 538.294 psi in the base cement to 1,267.898 psi with the addition of 4% BWOC, all meeting the API minimum standard of 500 psi. The addition of alum also accelerates the Initial Setting Time from 315 minutes to 15 minutes and the Final Setting Time from 430 minutes to 45 minutes. Based on the results of the study, an alum concentration of 3% BWOC provides the most optimal performance because it produces a high increase in compressive strength with a setting time that is still suitable for well cementing applications.